Adolescent perspectives on phase I cancer research1. Issue 5 (3rd October 2012) - Miller, Victoria A.; Baker, Justin N.; Leek, Angela C.; Hizlan, Sabahat; Rheingold, Susan R.; Yamokoski, Amy D.; Drotar, Dennis; Kodish, Eric
Abstract Background The aim of this study was to examine adolescent patients' perspectives on their understanding and decision making about a pediatric Phase I cancer study. Procedure Participants included adolescents ages 14–21 years with cancer (N = 20), all of whom attended a Phase I study consent conference. Participants responded to closed‐ and open‐ended questions on a verbally administered structured interview, which assessed aspects of understanding and decision making about the Phase I study. Results All participants decided to enroll in the Phase I study. The majority of participants understood that participation was voluntary, entailed risks, and that they could withdraw. Most also believed that participation in the Phase I study would increase the length of their lives. The most frequent reasons for enrolling were positive clinical benefit, needing an option, impact on quality of life, and few side effects or fewer than those of current or past treatments. Eighty‐five percent of participants reported that they themselves made the final decision about enrollment in the Phase I study. Conclusions Most participants hoped or expected that the Phase I study would provide a direct benefit (increased survival time or cure) and reported that they themselves were the final decision‐maker about enrollment. Clinicians may underestimate the role of adolescents, especially if they believe that parents typically make such decisions. Future research should assess the actual participation of children and adolescents during the informed consent process and explore the role of hope in their decision making about Phase I studies. Pediatr Blood Cancer 2013; 60: 873–878. © 2012 Wiley Periodicals, Inc.